1984
DOI: 10.1063/1.447389
|View full text |Cite
|
Sign up to set email alerts
|

Structural and magnetic properties of a copper–amino acid salt: Copper (II) bis (α-amino isobutyrato)

Abstract: ESR and ENDOR studies on the structure of primary oxidation products in irradiated αamino acids

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0
4

Year Published

1985
1985
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 26 publications
3
12
0
4
Order By: Relevance
“…There are many investigations of their properties but questions and controversies still exist. 22 Furthermore, even though many electron paramagnetic resonance (EPR) studies in copper-amino acid and peptide compounds have been reported, [23][24][25][26][27][28][29][30][31] single crystal studies of the more complex ternary copper amino acid compounds are scarce, 21,32 even when this is a sensitive spectroscopic technique to investigate the electronic structure of the metal ions and to estimate the weak interactions between them supported by the non-covalent couplings mentioned before. 31 Ternary compounds involving glycine, 1,10phenanthroline and copper nitrate or copper chloride, named [Cu(Gly)(phen)(H 2 O)]•NO 3 •1.5H 2 O (1) or [Cu(Gly)(phen)Cl] 2 •7H 2 O (2), having Cu II ions connected by paths including carboxylate and stacking interactions between Cu II ions were reported by Zhang et al 17 and Yodoshi et al 18 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…There are many investigations of their properties but questions and controversies still exist. 22 Furthermore, even though many electron paramagnetic resonance (EPR) studies in copper-amino acid and peptide compounds have been reported, [23][24][25][26][27][28][29][30][31] single crystal studies of the more complex ternary copper amino acid compounds are scarce, 21,32 even when this is a sensitive spectroscopic technique to investigate the electronic structure of the metal ions and to estimate the weak interactions between them supported by the non-covalent couplings mentioned before. 31 Ternary compounds involving glycine, 1,10phenanthroline and copper nitrate or copper chloride, named [Cu(Gly)(phen)(H 2 O)]•NO 3 •1.5H 2 O (1) or [Cu(Gly)(phen)Cl] 2 •7H 2 O (2), having Cu II ions connected by paths including carboxylate and stacking interactions between Cu II ions were reported by Zhang et al 17 and Yodoshi et al 18 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In most of the Cu 2+ doped compounds, the Cu 2+ ions replace divalent cations. Saccharin (sac) is extensively used as a non-caloric sweeting agent [6], and forms [M(sac) 2 -(H 2 0) 4 ]-2H 2 0 complexes, where M is a divalent metal ion, such as Fe 2+ , Co 2+ , Ni 2+ , Cu 2+ , and Zn 2+ [7], Single crystal X-ray analyses of these complexes reveal that they are isostructural and crystallize in the monoclinic space group P2j/c [7]. All the metal ions have octahedral geometry, surrounded by four water molecules and two saccharinate anions, (C 7 H 4 N0 3 S)~, by breaking a N-H bond, in the trans positions.…”
Section: Introductionmentioning
confidence: 99%
“…The hyperfine structure of copper is of interest as being the first to be discovered in the solid state by EPR method. Using paramagnetic ion as an impurity probe, one can study the behavior of paramagnetic ions and estimate the site symmetry of the ion present in the lattice [10][11][12][13]. The substitution of a divalent impurity ion in monovalent lattice has been subject by many researchers [14,15].…”
Section: Introductionmentioning
confidence: 99%